Testing loan loss provisioning hypotheses for Chinese banks - Li, Chenxi (2017)
ABSTRACT: This paper investigates loan loss provisions hypotheses concerning Chinese banks during the period of 2009 to 2016. I choose the income-smoothing, capital management, business cycle and x-efficiency hypotheses and test whether other control variables affect the provisioning behavior. When estimating the x-efficiency, it applies an independent model based on inputs and outputs variables to get the cost x-efficiency statistics. It also describes and analyzes Chinese banking system and relevant regulations, which also could affect the provisioning behavior.